Settlement of Criminal Actions Not Appearing Without Permission Through Military Discipline Legal Mechanism in Order Unit and Personnel Development - Nyoman Agus Surya Pradipta (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The law that applies specifically to military personnel consists of formal and material Military Criminal Law, apart from that there is also military discipline law which is regulated by law. Military crimes can be divided into two, namely pure military crimes and mixed military crimes. One of the pure military crimes is the crime of not being present without permission. The crime of being present without permission is generally regulated in CHAPTER III Book II of the Military Criminal Code, but this crime is also regulated in the Military Discipline Law as a violation of military discipline. With these conflicting legal regulations, the author then raises this problem into a thesis. The problem formulation that the author presents is: How is military disciplinary law applied to the crime of not being present without permission and what are the consequences of resolving THTI crimes through military disciplinary legal mechanisms in the face of unit and personnel development? There are three possibilities for resolving THTI crimes through military disciplinary legal channels. . The research method in this thesis is normative juridical using military discipline law enforcement theory, unit and personnel development theory and legal certainty theory. The conclusion of this research is that the criminal act of not being present without permission can be resolved through military disciplinary law, namely a criminal act in the narrow sense, namely Article 85 1 and Article 86 1 of the KUHPM. Completion of legal discipline will of course have an impact on the development of the unit and personnel concerned in the form of postponement of rank or education.